The crosstalk between H. pylori virulence factors and the PD1:PD-L1 immune checkpoint inhibitors in progression to gastric cancer - Aydın, Elif Merve; Demir, Tevriz Dilan; Seymen, Nogayhan; Said, Sawsan Sudqi; Oktem-Okullu, Sinem; Tiftikci, Arzu; Cicek, Bahattin; Tokat, Fatma; Tozun, Nurdan; Ince, Umit; Sezerman, Ugur; Sayi-Yazgan, Ayca (Elsevier BV, 2021)
The progression to gastric cancer has been linked to chronic infection with Helicobacter pylori (H. pylori). Immune checkpoint inhibitors (programmed cell death -1, PD-1; programmed cell death -ligand 1, PD-L1) have a role in cancer immune escape. The relationship between H. pylori virulence factors with PD-1, PD-L1 T helper 1 (Th1), T helper 17 (Th17), and regulatory T cell (Treg) response genes, has not been thoroughly investigated in the development of gastric cancer. Therefore, we evaluated how H. pylori virulence factors influence the expression levels of immune-related genes in the development of gastric immunopathology.A total of 92 gastric tissues of normal controls and patients with gastritis, gastric ulcer, and gastric cancer were examined for the expression of immune-checkpoint inhibitor genes (PD-1 PD-L1), Th1 (interferon- γ, IFN-γ), Th17 (interleukin- 17, IL-17, Retinoic-acid-receptor- related orphan nuclear receptor gamma t, RORγ-t), and Treg (Forkhead box P3, FOXP3) response genes with quantitative real-time PCR (qRT-PCR). Furthermore, correlation of H. pylori virulence factors' (cytotoxin-associated gene A, cagA; vacuolating cytotoxin gene A, vacA (s1,s2,m1,m2); blood group antigen-binding adhesin gene A, babA, duodenal ulcer promoting gene A, dupA; the putative neuraminyllactose-binding hemagglutinin homolog, hpaA; neutrophil-activating protein A napA; outer inflammatory protein A, oipA; urease A, ureA; and urease B, ureB) genotypes with a degree of inflammation and density of H. pylori were investigated. Next, the relationship between H. pylori virulence factors and immune-checkpoint inhibitor genes, and T-cell response genes was evaluated. Eventually, a decision tree model was developed to determine the clinical outcome of patients using expression data.The intensity of PD-1 and PD-L1 mRNA expression was increased significantly in gastric tissue of patients with gastric ulcer (PD-1: 2.3 fold, p=0.01; PD-L1: 2.1 fold, p=0.004), and gastric cancer (PD-1: 2 fold, p= 0.04; PD-L1: 1.8 fold, p=0.05) compared with control subjects. Also, PD-1: PD-L1 expression was significantly higher in patients with gastritis, who were infected with a marked density of H. pylori compared with its mildly infected counterparts. Furthermore, a novel negative correlation was found between PD-1 (r= -0.43) and PD-L1 (r= -0.42) with FOXP3 in patients with gastritis. CagA-positive H. pylori strain's negative association with PD-L1 expression (r=-0.34) was detected in patients with gastritis. Interestingly, PD-1 mRNA expression correlated positively with vacA s2/m2, in gastritis (r=0.43) and ulcer (r=0.43) patients. Furthermore, PD-1: PDL1 expression negatively correlated with vacA m1/m2 (r=-0.43 for PD-1; r=-0.38 for PD-L1) in gastritis patients. Moreover, an inverse correlation of PDL1 was present with vacA m1 (r=0.52) and vacA s1/m1 (r=0.46) versus vacA m2 (r=-0.44) and vacA m1 (r=0.52) and vacA s1/m2 (r=-0.14) in ulcer patients, respectively. Also, a correlation of vacA m2 (r=-0.47) and vacA s1/s2 (r= 0.45) with PD-1 was detected in ulcer patients. In addition, a novel negative correlation between FOXP3 mRNA levels and napA was shown in patients with gastritis and ulcer (r=-0.59). Finally, a computer-based model that was developed showed that knowing the expression levels of PD-L1, RORγ-t, and vacA s1/m2 would be useful to detect the clinical outcome of a patient.Our results suggested that PD-1:PD-L1 immune checkpoint inhibitors were increased in gastric pre-cancerous lesions that progress to gastric cancer. Herein, we report the relationship between H. pylori virulence factors and expression of host immune checkpoint inhibitors for diagnostic prediction of gastric malignancies using computer-based models.
Keywords: Adult; Aged, 80 and over; CD4-Positive T-Lymphocytes; Male; Helicobacter pylori; Biopsy; Programmed Cell Death 1 Receptor; Middle Aged; B7-H1 Antigen; Helicobacter Infections; Bacterial Proteins; Gastric Mucosa; Stomach Neoplasms; Gastritis; Biomarkers, Tumor; Disease Progression; Humans; Female; Aged; Signal Transduction